The Influence of the School Principal’s Leadership Style and Teacher’s Motivation on Teacher’s Discipline in SMP Negeri at Penukal Utara District - Apriani, Wari (Journal of Social Work and Science Education, 2023)
This study aimed to determine the influence of the principal’s leadership style and the teacher’s motivation on the discipline of SMP Negeri teachers in Penukal Utara District. This type of research was quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all SMP Negeri teachers in Penukal Utara District, consisting of 97 teachers. Data collection techniques used a questionnaire data analysis techniques include quantitative descriptive analysis techniques and multiple regression. The results of this study stated that 1) there was a significant influence of the principal’s leadership style on the discipline of teachers in SMP Negeri in Penukal Utara District; 2) there was a significant influence of teacher motivation on the discipline of SMP Negeri teachers in Penukal Utara District; and 3) there was a jointly significant influence of the principal’s leadership style and teacher’s motivation on the discipline of teachers of SMP Negeri in Penukal Utara District.